Mithrax hispidus (Herbst) e Mithrax tortugae Rathbun novos registros de Brachyura (Decapoda, Majidae) para o litoral de Santa Catarina, Brasil. - Rieger, Paulo Juarez (2001)
They are registered for the first time in the South Brazilian coast, the crabs Milhrax hispidlls (Herbst, 1790) and Milhrax lorillgae Rathbun, 1920, which previous Southern limit of di stribution were at Siio Paulo State and now it is extended to the Santa Catarina State coast line.